Modeling mathematical critical thinking and connection abilities as predictors of spatial ability in pre-service mathematics teachers - Nurma Izzati; Aditiya Eka Nugraha (Universitas Muhammadiyah Surakarta, 2026)
Spatial ability plays a crucial role in geometry learning, yet its cognitive predictors within higher education contexts remain underexplored. While prior research has established associations between spatial reasoning and mathematical performance, limited studies have examined the combined predictive roles of mathematical critical thinking and mathematical connection abilities within a single regression framework. This study investigates the structural predictive influence of these two cognitive constructs on students’ mathematical spatial ability among pre-service mathematics teachers. A quantitative explanatory correlational design was employed, involving all 23 students enrolled in a Spatial Geometry course at UIN Siber Syekh Nurjati Cirebon during the 2025/2026 academic year. The sample represented a census of the accessible cohort, as the entire population meeting the inclusion criteria was included. Data were collected using validated essay-based instruments aligned with established theoretical indicators. Multiple regression analysis was conducted after verifying statistical assumptions. The results indicate that mathematical critical thinking ability significantly predicts mathematical spatial ability (p = 0.001), and mathematical connection ability also demonstrates a significant positive predictive role (p = 0.000). Jointly, both predictors explain 81.1% of the variance in spatial ability (Adjusted R² = 0.811). These findings highlight the integrative contribution of analytical reasoning and conceptual linkage processes to spatial cognition and suggest that geometry instruction may benefit from systematically fostering critical thinking and mathematical connections.